Household-scale anaerobic digestion of food waste—a community case study from Bozeman, Montana - Roland Ebel; Jed Eberly; Bruna Irene Grimberg; Tim Seipel; Fabian D. Menalled (Frontiers in Sustainable Food Systems)
IntroductionOne-third of food in the United States is wasted, creating significant environmental and social challenges which anaerobic digestion (AD) can address by converting that waste into a nutrient-rich digestate suitable for use as a biofertilizer. While AD is commonly used in municipal and industrial-scale operations for obtaining biogas, household-scale AD to generate of biofertilizer is a promising on-site option without the infrastructure and process complexities associated with large-scale systems.MethodsThis community-based case study investigated the characteristics of food waste and digestate nutrient content from two household-scale AD designs. Digesters were deployed in 12 households (six households used commercial digesters and six used a smaller custom-built prototype) in Bozeman, Montana, USA. Food waste was collected from households, separated by categories, and nutrient content was determined.Results and discussionOver 12 weeks of digester operation, the nutrient content of the digestate was measured. It changed during digester operation with N, P, K, S, pH, and conductivity all increasing (p < 0.05) over time. While food waste C:N ratios varied from 12.1 to 25.7, the C:N ratio of digestate was significantly lower (p < 0.001), with a mean C:N ratio of 6.6. Digestate ammonia levels remained low (< 60 mg l−1) and below inhibitory thresholds during the collection period, but the ratio of NH3-N to total N increased from 0.09 in the food waste to 0.25 in the digestate. Digestate C and N content did not differ between digester models, while different pH (p < 0.05) was observed with a final pH of 6.1 in the commercial small-scale digester and a pH of 5.3 in the custom-built prototype. A survey of participating households revealed that 64% of respondents gained a new awareness of the volume of food waste they generated, and 87% expressed a willingness to recommend biodigesters despite challenges related to convenience and using this technology in a cold climate. Participants perceived the custom-built digester as more user-friendly than the commercial one. This case study highlights the potential of household-scale AD systems to generate biofertilizer, emphasizing the importance of user-friendliness and design tailored to household needs, generated feedstock, and environmental conditions.